High-performance FPGA implementation of the secure hash algorithm 3 for single and multi-message processing - Fatimazahraa Assad; Mohamed Fettach; Fadwa El Otmani; Abderrahim Tragha (Institute of Advanced Engineering and Science, 2022)
The secure hash function has become the default choice for information security, especially in applications that require data storing or manipulation. Consequently, optimized implementations of these functions in terms of Throughput or Area are in high demand. In this work we propose a new conception of the secure hash algorithm 3 (SHA-3), which aim to increase the performance of this function by using pipelining, four types of pipelining are proposed two, three, four, and six pipelining stages. This approach allows us to design data paths of SHA-3 with higher Throughput and higher clock frequencies. The design reaches a maximum Throughput of 102.98 Gbps on Virtex 5 and 115.124 Gbps on Virtex 6 in the case of the 6 stages, for 512 bits output length. Although the utilization of the resource increase with the increase of the number of the cores used in each one of the cases. The proposed designs are coded in very high-speed integrated circuits program (VHSIC) hardware description language (VHDL) and implemented in Xilinx Virtex-5 and Virtex-6 A field-programmable gate array (FPGA) devices and compared to existing FPGA implementations.